A review of the Macropes Motschulsky (Hemiptera: Lygaeoidea: Blissidae) from China, with descriptions of three new species - Gao, Cuiqing; Bu, Wenjun (Zootaxa, 2010)
Eighteen species of the genus Macropes Motschulsky from China are treated in the paper, in which M. varipennis (Walker, 1872) and M. dilutus Distant, 1901 are newly recorded from China; M. bambusiphilus Zheng & Zou, 1982 and M. slateri Zheng & Wang, 1987 are treated as new junior synonymies of M. robustus Zheng & Zou, 1982; three of them, M. complanus sp. nov., M. testaceus sp. nov., and M. peculiaris sp. nov., are described as new to science. Photographs of all eighteen species and drawings of genitalia of new species and newly recorded species from China are illustrated, along with those modified parts of the key to the World species of Macropes in Slater (1979). The type specimens of the new species are deposited in the Institute of Entomology, College of Life Sciences, Nankai University, Tianjin, China.